Digital Literacy Training Based on Local Wisdom through a Digital Dictionary of Papuan Regional Languages to Preserve Sentani Language in Waibu District, Papua: Pelatihan Literasi Digital Berbasis Kearifan Lokal melalui Kamus Digital Bahasa Daerah Papua untuk Melestarikan Bahasa Sentanidi Distrik Waibu, Papua - Hasan*, Nur Fitrianingsih; Mulyadi, Achmad Akbar Sanjaya; Aisyah, Aisyah (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
The threat of extinction of Papuan regional languages ​​has given rise to Perbup policy Number 21 of 2021 concerning the implementation of local mother tongue curriculum learning in Papua. This PKM activity aims to increase digital literacy through the use of the Papuan Regional Language Digital Dictionary and the interactive mulok media portal as a mulok learning reference for teachers and students at SDN Inpres Doyo Lama, Waibu District, Sentani, Papua so as to preserve the mother tongue which is almost extinct. Several solutions to problems that are considered to be partners' priorities are resolved through socialization methods, transfer of science and technology, appropriate technology (TTG), training & mentoring on the use of TTG and evaluation of PKM activities. The results of this service activity had a positive impact on partners with interval values ​​for the technology infrastructure aspect of 80-90%, the digital literacy aspect of 80-90% and the digital skills aspect of 60-78% according to the results of the participant questionnaire. Strengthening is needed to further improve partners' digital skills through knowledge transfer efforts through technical guidebooks for TTG management so that partners' skills increase continuously and independently.